Application of the Constitutional Court's decision on the recognition of the flow of trust in Indonesia in order to realize SDG's 2030 points 16 (Peace, Justice, and Strong Institution) Case Study in Cening Village, Singorojo District, Kendal Regency - Wira Pradana, Tirta Mulya (Lex Scientia Law Review, 2018)
Intolerance and discrimination based on religion and belief, by the United Nations in "Declaration on the Elimination of All Forms of Intoles and Discrimination Based on Religion or Belief", is interpreted as any distinction, neglect, prohibition or prevention based on religion or belief in its purpose or As a result, eliminating or reducing the recognition, enjoyment, or implementation of human rights and fundamental freedoms on equal basis. As a state based on law, Indonesia highly respects and upholds the existence of human rights. In the second principle of Pancasila, it is explained that the Indonesian state recognizes and respects the attitude of "fair and civilized humanity". And reinforced from the 5th precepts of Pancasila, namely "Social Justice for all Indonesian people" thus in a real and philosophical manner, Indonesia has a strong ideal to uphold human rights in accordance with the provisions of the law both individual and group human rights for the realization of justice social for all Indonesian people.